Chicano Frankenstein - Olivas, Daniel A. (Forest Avenue Press LLC, 2024)
"An unnamed paralegal, brought back to life through a controversial process, maneuvers through a near-future world that both needs and resents him. As the United States president spouts anti-reanimation rhetoric and giant pharmaceutical companies rake in profits, the man falls in love with lawyer Faustina Godínez. His world expands as he meets her network of family and friends, setting him on a course to discover his first-life history, which the reanimation process erased. With elements of science fiction, horror, political satire and romance, Chicano Frankenstein confronts our nation's bigotries and the question of what it truly means to be human."--